PRACTICAL TECHNOLOGICAL SYSTEM OF THE ACMEOLOGICAL APPROACH IN THE FORMATION OF THE BASIC COMPETENCIES OF WORKING WITH INFORMATION IN THE EDUCATIONAL PROCESS OF STUDENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In this article, based on the acmeological approach, some opinions are expressed about the pedagogical, psychological and methodological features of forming the basic competencies of working with information in students. Also, in the article, the acmeological approach and its features, issues of its formation in the individual, and its compatibility with the competence of working with information are pedagogically analyzed.